Identifying opinion leaders and narrative agency in the rejection omnibus law discourse - Hari Fitrianto; Muzaqqi, Fahrul (Faculty of Communications Science, Dr. Soetomo University, 2023)
As a social media platform, Twitter can become an arena for civil citizens to contest the state discourse. The rejection of the Omnibus Law Bill proves the legitimacy of the massive resistance and mass mobilisation to reject policy products that contradict the public interest. This research was meant to provide a social media analysis of the issues of the plan of legitimation of the Omnibus Law Bill by employing two analysis methods: social network analysis and descriptive qualitative method. Twitter interactions during the Omnibus Law Bill rejection era were dominated by civil actors. The primary activity on Twitter was not only civil movements but also confronting individuals who could help to form public ideas. Within the agency’s narrative framework, Twitter interactions related to Omnibus Law Bill are communal and social endeavours as part of participation in digital activism. Other dictions were also visible within various hashtags constructed to assert the agent’s political position. Various content and digital media platform were produced as the media for transferring information and knowledge. They were put for the best use in a beautiful package. By opinion leaders’ agency, the narrative built by the State can be contested to influence others.